Globalization on The Railway Transport Sector - Tryson Yangailo (Universitas Prasetiya Mulya, 2022)
This research examined the impact and challenges of globalization on railway transport sector in Africa. The study employed two railway companies as sample, state-owned railway company and private owned company. Using questionnaire as research instruments, data were collected and analyzed with simple percentages and non-parametric Kruskal-Wallis statistical tools. The major findings of the study were that: (a) the problem of competition and poor technology are the greatest challenges; (b) Railway companies with fewer globalization challenges perform significantly much better than those with more challenges; (c) Managers with positive attitude toward globalization perform significantly better than those with negative attitude and; (d) Railway state-owned receives government’s support but not enough to warrant its competitiveness. The study concluded that for railway sector to continue surviving in this globalization era, governments must immediately step up and render support to railway transport sector as opposed to only supporting road sector.